Pharmacological Properties of a Low Molecular Weight Butyryl Heparin Derivative (C4-CY 216) with Long Lasting Effects - Saivin, S; Petitou, M; Lormeau, J C; Dupouy, D; Sié, P; Caranobe, C; Houin, G; Boneu, B (Thrombosis and Haemostasis, 1992)
We have investigated the pharmacological properties of an O-acylated butyryl derivative of the low molecular weight heparin CY 216 (C4-CY 216). In a purified system the ability of C4-CY 216 to catalyze thrombin and factor Xa inhibition was comparable to that of CY 216. The antithrombin and antifactor Xa catalytic efficiencies of C4-CY 216 were reduced 217 and 12 times respectively when albumin (10 mg ml-1) was added to the reagents, while those of CY 216 were essentially unchanged. In plasma, the antifactor Xa specific activity of C4-CY 216 was close to that of CY 216 but the antithrombin specific activity was 2 times lower. After bolus and continuous intravenous injection to rabbits, the clearances of the two activities of C4-CY 216 were on average half the corresponding values of CY 216. After subcutaneous injection, the bioavailability of C4-CY 216 was comparable to that of CY 216. C4-CY 216 was as potent as CY 216 in preventing venous thrombosis in the thromboplastin-Wessler model and the duration of the antithrombotic effect was longer than that of the parent compound. The chemical alteration of CY 216 did not enhance the prohaemorrhagic effect in the rat tail transection model. Therefore, the new concept of heparin derivative having a low clearance and long lasting effects that we have recently reported for unfractionated heparin may also be applied to a low molecular weight heparin.